Agrivoltaics: The future of electricity supply arrangement from the perspective of German entrepreneurial farmers - Bauknecht Martin (E3S Web of Conferences)
The framework of the Renewable Energy Sources Act (EEG) has enabled the successful expansion of solar energy to date. But is the rigid model with a fixed feed-in tariff still up to date? A decentralized energy system is modeled to create an electricity self-sufficient village using agrivoltaics. Energy sharing among citizens, commercials, municipalities, and farmers creates a self-managed energy community. Farmers play a key role in this dual land use. This article examines the central research question of what the future of the electricity supply arrangement should look like from the perspective of entrepreneurial farmers. The study draws on a survey of 215 German farmers. Of these, 159 responses came from entrepreneurial farmers, which are analyzed. The survey results show a trend toward more flexible future electricity supply arrangements, enabling customized marketing of the business model. Several policy implications can be formulated to support the realization of an electricity self-sufficient village using agrivoltaics. In the first step, electricity self-sufficiency is aimed in the sunny months from March to October, until cross-seasonal storage media are available and ready for series production.